A method for electroless plating of palladium-free nickel-tin-phosphorus alloy on PCB copper-clad plate and a PCB copper-clad plate prepared by the method

CN122773330APending Publication Date: 2026-09-18NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610996763.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-09-18

AI Technical Summary

Technical Problem

[0003]然而,这种依赖钯活化的化学镀镍工艺存在多重缺陷

Benefits of technology

(1)本发明采用含有二甲胺基硼烷的无钯预镀镍活化液,直接在PCB覆铜板铜表面沉积一层具有自催化活性的薄镍层,完全替代了传统化学镀镍工艺中必不可少的贵金属钯活化步骤。该工艺避免了因钯价格昂贵且波动剧烈带来的高成本问题,同时避免了钯活化液对杂质敏感、使用寿命短、工艺窗口窄等工艺控制难题,减少了含钯废水的产生与处理负担,具有良好的经济效益和环境友好性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122773330A_ABST
    Figure CN122773330A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of printed circuit board manufacturing, and particularly relates to a method for palladium-free electroless plating of nickel-tin-phosphorus alloy on a PCB copper-clad plate and a PCB copper-clad plate prepared by the method. The method comprises the following steps: immersing the PCB copper-clad plate into a palladium-free pre-plating nickel activating solution to perform pre-plating nickel treatment, so as to obtain a PCB copper-clad plate with a nickel layer; the palladium-free pre-plating nickel activating solution comprises dimethylamine borane; immersing the PCB copper-clad plate with the nickel layer into an electroless plating nickel-tin-phosphorus solution to perform electroless plating treatment, so as to obtain a PCB copper-clad plate with a deposited nickel-tin-phosphorus ternary alloy plating layer. The present application directly deposits a nickel layer with self-catalytic activity on the copper surface by using a palladium-free pre-plating nickel activating solution containing dimethylamine borane to replace palladium activation, and then deposits a nickel-tin-phosphorus ternary alloy plating layer on the nickel layer, so as to realize cost reduction, environmental burden reduction and obtain a plating layer with good comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of printed circuit board manufacturing technology, and in particular to a method for palladium-free electroless plating of nickel-tin-phosphorus alloy on copper-clad laminates (PCBs) and the PCB copper-clad laminates prepared therefrom. Background Technology

[0002] In the manufacturing process of printed circuit boards (PCBs), surface treatment of exposed copper circuitry is a critical step to ensure its solderability, corrosion resistance, and long-term reliability. Currently, electroless nickel / gold plating (ENIG) and electroless nickel / palladium / gold plating (ENEPIG) are the most widely used surface treatment technologies in this field. In these technologies, a layer of electroless nickel plating is typically deposited on the copper surface first as a barrier layer and underlayer. However, the copper surface itself does not possess the autocatalytic activity to directly initiate the electroless nickel plating reaction. Therefore, existing technologies generally rely on the noble metal palladium (Pd) for activation treatment: in a palladium salt solution, palladium catalytic nuclei are formed on the copper surface, thereby initiating the subsequent deposition of nickel.

[0003] However, this palladium-activated electroless nickel plating process has several drawbacks. First, palladium is a precious metal, with a high and volatile price, resulting in high raw material costs for PCB surface treatment. Second, the palladium activation solution is sensitive to impurities, has a short lifespan, a narrow process window, and is prone to problems such as incomplete plating or poor adhesion due to uneven activation. Furthermore, palladium is a heavy metal, and the treatment of palladium-containing wastewater is difficult and costly, causing a significant environmental burden.

[0004] Therefore, developing a novel process that can eliminate the palladium activation step and impart a composite coating to the copper surface with excellent corrosion resistance, high adhesion and good solderability has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The purpose of this invention is to address the problems existing in the prior art by providing a method for palladium-free electroless nickel-tin-phosphorus alloy plating on PCB copper-clad laminates and the PCB copper-clad laminate prepared therefrom. By using a palladium-free pre-plating nickel activation solution containing dimethylaminoborane to directly deposit a self-catalytically active nickel layer on the copper surface instead of palladium activation, and then depositing a nickel-tin-phosphorus ternary alloy plating layer on this nickel layer, costs are reduced, environmental burden is decreased, and a plating layer with excellent overall performance is obtained.

[0006] To achieve the above objectives, the present invention provides a method for palladium-free electroless plating of nickel-tin-phosphorus alloy on a PCB copper-clad laminate, comprising the following steps: S1. Immerse the PCB copper-clad board in a palladium-free pre-plating nickel activation solution for pre-plating nickel to obtain a PCB copper-clad board with a nickel layer; the palladium-free pre-plating nickel activation solution includes dimethylaminoborane. S2. Immerse the PCB copper-clad board with a nickel layer into a chemical nickel-tin-phosphorus plating solution for chemical plating treatment to obtain a PCB copper-clad board with a nickel-tin-phosphorus ternary alloy plating layer deposited on it.

[0007] In an optional embodiment, in S1, the palladium-free pre-plating nickel activating solution comprises the following components: 20-40 g / L nickel sulfate, 20-30 g / L boric acid, 20-30 g / L ammonium chloride, 20-40 g / L citrate, and 1-5 g / L dimethylaminoborane.

[0008] In an optional embodiment, the citrate includes at least one of ammonium citrate and sodium citrate.

[0009] In an optional embodiment, in S1, the pre-nickel plating treatment is performed at a temperature of 50-70°C, a pH of 7-9, and a time of 3-5 minutes. After the pre-nickel plating treatment, the sample is rinsed with water for 10-15 seconds before proceeding to S2.

[0010] In an optional embodiment, in S2, the electroless nickel-tin-phosphorus plating solution comprises the following components: nickel sulfate 20-40 g / L, sodium stannate 15-30 g / L, sodium hypophosphite 50-70 g / L, lactic acid 60-100 mL / L, gluconic acid 10-30 mL / L, and ammonium sulfate 50-80 g / L.

[0011] In an optional embodiment, in step S2, the electroless plating process is carried out under stirring conditions, with the stirring speed being 300-600 r / min; the temperature of the electroless plating process is 45-55℃, the pH is 6.5-7.5, and the time is 10-20 min. After the electroless plating process, the plated board is washed with water for 10-15 s, then washed with alcohol for 3-10 s, and finally dried at 55-65℃ for 20-30 min to obtain a PCB copper-clad board with a nickel-tin-phosphorus ternary alloy plating layer deposited on it.

[0012] In an optional embodiment, S1 further includes a step of sequentially degreasing and micro-etching the PCB copper-clad board before immersing it in a palladium-free pre-plating nickel activation solution.

[0013] In an optional embodiment, the degreasing treatment is carried out in a degreasing solution comprising the following components: sodium hydroxide 5-15 g / L, sodium carbonate 10-30 g / L, sodium silicate 5-10 g / L, and sodium phosphate 10-30 g / L; the degreasing treatment is performed at a temperature of 60-70°C for 2-5 minutes. After the degreasing treatment, the sample is rinsed with water for 10-15 seconds, followed by micro-etching.

[0014] In an optional embodiment, the micro-etching treatment is carried out in a micro-etching solution comprising the following components: 10-20 g / L sulfuric acid solution and 20-40 g / L sodium persulfate; the sulfuric acid solution has a mass fraction of 96-98%; the micro-etching treatment is performed at a temperature of 10-25°C for 30-60 seconds. After the micro-etching treatment, the sample is rinsed with water for 10-15 seconds, and then immersed in a palladium-free pre-plating nickel activation solution for pre-plating nickel.

[0015] In one alternative implementation, the next step is performed immediately after each step is completed to prevent the copper-clad PCB from oxidizing in the air.

[0016] In an optional implementation, in S1 and S2, when the PCB copper-clad laminate cannot be completely submerged due to the drop in liquid level caused by evaporation of the plating solution, deionized water should be added until the PCB copper-clad laminate is completely submerged.

[0017] The present invention also provides a copper-clad PCB prepared according to the method, wherein the surface of the copper-clad PCB has a nickel-tin-phosphorus ternary alloy plating formed by the method.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses a palladium-free pre-plating nickel activation solution containing dimethylaminoborane to directly deposit a thin nickel layer with autocatalytic activity on the copper surface of a PCB copper-clad laminate, completely replacing the essential palladium activation step in the traditional electroless nickel plating process. This process avoids the high cost problem caused by the expensive and volatile price of palladium, and also avoids the process control problems such as the palladium activation solution's sensitivity to impurities, short service life, and narrow process window. It also reduces the generation and treatment burden of palladium-containing wastewater, and has good economic benefits and environmental friendliness.

[0019] (2) The nickel-tin-phosphorus ternary alloy coating deposited on the basis of the pre-plated nickel layer in this invention makes full use of the advantages of tin. Compared with the traditional electroless nickel-phosphorus (Ni-P) coating, the coating of this invention has significantly improved hardness and good corrosion resistance. At the same time, the presence of tin effectively improves the solderability of the coating surface, which can meet the requirements of subsequent component assembly on the PCB for welding reliability.

[0020] (3) In this invention, dimethylaminoborane is used as the reducing agent in the pre-plating nickel step. It has strong reducing power and moderate deposition rate, and can form a dense, uniform, and controllable initial nickel layer on the copper surface, avoiding problems such as incomplete plating and poor adhesion caused by uneven distribution of palladium particles in traditional palladium activation. SEM observation shows that the obtained plating layer has a uniform and dense surface without obvious defects such as cracks and pinholes. The pre-plated nickel layer has good compatibility with the subsequent Ni-Sn-P electroless plating solution, ensuring the overall consistency and stability of the composite plating layer, and has good adhesion to the copper substrate.

[0021] (4) The chemical plating process provided by this invention has clear steps, low equipment requirements, a wide process window, and is easy to control and operate, making it suitable for large-scale assembly line production in the PCB industry. At the same time, the method of this invention does not require the use of palladium catalyst, avoiding cross-contamination of the plating solution that palladium may cause, and has good process stability, providing a new low-cost, high-performance, and environmentally friendly solution for PCB surface treatment. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the process of palladium-free electroless nickel-tin-phosphorus alloy plating on a PCB copper-clad board in Embodiment 1 of the present invention; Figure 2 These are hardness comparison diagrams of the alloy coatings obtained in Examples 1-4 and Comparative Examples 1-2 of this invention; Figure 3 This is a SEM image of the alloy coating obtained in Example 3 of the present invention. Figure 3 (a) is the SEM image at a scale bar of 20 μm. Figure 3 (b) is the SEM image at a scale bar of 10 μm; Figure 4 This is an elemental distribution diagram of the alloy coating obtained in Example 3 of the present invention. Figure 4 In the figure, 'a' represents the comprehensive distribution map. Figure 4 In the diagram, 'b' represents the distribution of nickel (Ni) element. Figure 4 In the diagram, 'c' represents the distribution of phosphorus (P). Figure 4 In the diagram, d represents the distribution of tin (Sn) elements. Detailed Implementation

[0023] The following embodiments are provided to better understand the present invention and are not limited to the described embodiments. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0024] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0025] In the following embodiments and comparative examples of the present invention, the PCB copper-clad board is an FR-4 PCB copper-clad board with a size of 15mm × 15mm.

[0026] Example 1 This embodiment provides a method for palladium-free electroless plating of nickel-tin-phosphorus alloy on a PCB copper-clad laminate, including the following steps: (1) Pretreatment of PCB copper clad laminate Drill holes at the corners of the copper-clad PCB to facilitate hanging and subsequent operations.

[0027] (2) Preparation of degreasing solution The formula is: NaOH 10g / L, Na2CO3 20g / L, Na2SiO3 7.5g / L, Na3PO4·12H2O 20g / L.

[0028] The preparation steps are as follows: Weigh 2g NaOH, 4g Na2CO3, 1.5g Na2SiO3, and 4g Na3PO4·12H2O, dissolve them separately in a small amount of deionized water, and then pour them into a 250mL beaker. Add deionized water to the 200mL mark, stir well, and you will get the degreasing solution.

[0029] (3) Preparation of micro-etching solution The formula is: 15 g / L of 98% sulfuric acid solution and 30 g / L of Na2S2O8.

[0030] The preparation steps are as follows: Measure 3g of 98% sulfuric acid solution and slowly add it dropwise to 100mL of deionized water for dilution; separately weigh 6g of Na2S2O8 and dissolve it in a small amount of deionized water. Mix the two solutions in a 250mL beaker, add deionized water to the 200mL mark, and stir well to obtain the micro-etching solution.

[0031] (4) Prepare palladium-free pre-plating nickel activation solution The formula is: NiSO4·7H2O 30g / L, H3BO3 25g / L, NH4Cl 25g / L, ammonium citrate 30g / L, dimethylaminoborane 3g / L.

[0032] The preparation steps are as follows: Weigh 6g NiSO4·7H2O, 5g H3BO3, and 5g NH4Cl, dissolve them separately in a small amount of deionized water, and pour them into a 250mL beaker. Add deionized water to bring the volume to 150mL. Add 6g ammonium citrate and stir to dissolve. Adjust the pH to 8 with NaOH solution. Separately weigh 0.6g dimethylaminoborane, dissolve it in a small amount of deionized water, and slowly add it to the above mixture while stirring. Add deionized water to the 200mL mark, and finely adjust the pH to 8 again to obtain the palladium-free pre-plating nickel activation solution.

[0033] (5) Preparation of chemical nickel-tin-phosphorus plating solution The formula is as follows: NiSO4·6H2O 30g / L, Na2SnO3·4H2O 15g / L, NaH2PO2·H2O 60g / L, lactic acid 80mL / L, gluconic acid 20mL / L, (NH4)2SO4 65g / L.

[0034] The preparation steps are as follows: Weigh 6g NiSO4·6H2O and 13g (NH4)2SO4, dissolve them separately in a small amount of deionized water, pour them into a 250mL beaker, and add deionized water to bring the volume to 150mL. Add 16mL lactic acid and 4mL gluconic acid, and stir to mix well. Separately weigh 3g Na2SnO3·4H2O, add a small amount of deionized water and an appropriate amount of NaOH to dissolve it completely, and slowly add it to the above mixture while stirring. Adjust the pH to 7 with NaOH solution. Weigh 12g NaH2PO2·H2O, dissolve it in a small amount of deionized water, and slowly add it to the pH-adjusted mixture while stirring. Add deionized water to the 200mL mark, and finely adjust the pH to 7 again to obtain the electroless nickel-tin-phosphorus plating solution.

[0035] (6) Palladium-free electroless nickel-tin-phosphorus alloy plating on copper-clad PCB boards The PCB copper-clad laminate was immersed in a degreasing solution at 65°C for 3.5 minutes, then rinsed with deionized water for 15 seconds. The degreased copper-clad laminate was then immersed in a micro-etching solution at 25°C for 45 seconds, then rinsed with deionized water for 10 seconds. The micro-etched copper-clad laminate was then immersed in a palladium-free pre-plating nickel activation solution at 60°C for 4 minutes, then rinsed with deionized water for 10 seconds. The pre-plated nickel copper-clad laminate was then immersed in a chemical nickel-tin-phosphorus plating solution at 50°C with magnetic stirring at 500 rpm for 15 minutes. After plating, the copper-clad laminate was removed, rinsed with deionized water for 10 seconds, and then washed with alcohol for 5 seconds. The washed copper-clad laminate was then placed in a 60°C heating oven to dry for 20 minutes, and then removed to obtain a PCB copper-clad laminate with a nickel-tin-phosphorus ternary alloy plating layer deposited on its surface.

[0036] Example 1 shows a schematic diagram of the process for palladium-free electroless nickel-tin-phosphorus alloy plating on a PCB copper-clad laminate, as follows: Figure 1 As shown.

[0037] Example 2 The only difference between this embodiment and Example 1 is that the concentration of Na2SnO3·4H2O in the electroless nickel-tin-phosphorus plating solution is 20 g / L. Correspondingly, the amount of Na2SnO3·4H2O weighed in the preparation step is adjusted to 4 g.

[0038] The remaining steps are exactly the same as in Example 1.

[0039] Example 3 The only difference between this embodiment and Example 1 is that the concentration of Na2SnO3·4H2O in the electroless nickel-tin-phosphorus plating solution is 25 g / L. Correspondingly, the amount of Na2SnO3·4H2O weighed in the preparation step is adjusted to 5 g.

[0040] The remaining steps are exactly the same as in Example 1.

[0041] Example 4 The only difference between this embodiment and Example 1 is that the concentration of Na2SnO3·4H2O in the electroless nickel-tin-phosphorus plating solution is 30 g / L. Correspondingly, the amount of Na2SnO3·4H2O weighed in the preparation step is adjusted to 6 g.

[0042] The remaining steps are exactly the same as in Example 1.

[0043] Comparative Example 1 The only difference between this comparative example and Example 1 is that the concentration of Na2SnO3·4H2O in the electroless nickel-tin-phosphorus plating solution is 0 g / L. Accordingly, the weighing and addition of Na2SnO3·4H2O in the preparation steps are omitted.

[0044] The remaining steps are exactly the same as in Example 1.

[0045] Comparative Example 2 This comparative example provides a method for chemically plating a nickel-tin-phosphorus alloy onto a copper-clad PCB, including the following steps: (1) Pretreatment of PCB copper clad laminate Same as Example 1.

[0046] (2) Preparation of degreasing solution Same as Example 1.

[0047] (3) Preparation of micro-etching solution Same as Example 1.

[0048] (4) Preparation of palladium activation solution The formula is: 0.1 g / L PdCl2 and 10 mL / L of 37% hydrochloric acid solution.

[0049] The preparation steps are as follows: Weigh 0.01g of PdCl2 and dissolve it in a small amount of deionized water. Measure 1mL of 37% hydrochloric acid solution and slowly add it dropwise to 50mL of deionized water for dilution. Mix the two solutions in a 150mL beaker, add deionized water to the 100mL mark, and stir well to obtain the palladium activated solution.

[0050] (5) Preparation of chemical nickel-tin-phosphorus plating solution Same as Example 3.

[0051] (6) Electroless plating of nickel-tin-phosphorus alloy on PCB copper-clad laminate The PCB copper-clad laminate was immersed in a degreasing solution at 65°C for 3.5 minutes, then rinsed with deionized water for 15 seconds. The degreased copper-clad laminate was then immersed in a micro-etching solution at 25°C for 45 seconds, then rinsed with deionized water for 10 seconds. The micro-etched copper-clad laminate was then immersed in a palladium activation solution at 35°C for 1 minute, then rinsed with deionized water for 10 seconds. The activated copper-clad laminate was then immersed in a chemical nickel-tin-phosphorus plating solution at 50°C with magnetic stirring at 500 rpm for 15 minutes. After plating, the copper-clad laminate was removed, rinsed with deionized water for 10 seconds, and then washed with alcohol for 5 seconds. The washed copper-clad laminate was then placed in a heating oven at 60°C for 20 minutes to dry, and then removed to obtain a PCB copper-clad laminate with a nickel-tin-phosphorus ternary alloy plating layer deposited on its surface.

[0052] Experimental Example 1 Hardness tests were performed on the alloy plating layers on the surfaces of the PCB copper-clad laminates prepared in Examples 1-4 and Comparative Examples 1-2, respectively. The tests were conducted using a digital Vickers hardness tester (Shanghai Kaiyan Testing Instruments Co., Ltd.). A comparison chart of the hardness of the alloy plating layers obtained in Examples 1-4 and Comparative Examples 1-2 was obtained, as shown below. Figure 2 As shown. Among them, the coating obtained in Example 2 has the highest hardness, at 163.3 HV; the hardness of Comparative Example 1 (without sodium stannate, i.e., Ni-P coating) is 131.6 HV; and the hardness of the Ni-Sn-P coating obtained in Comparative Example 2 (using the conventional palladium activation process) is 141.9 HV.

[0053] The results show that the coating hardness of the embodiment of the present invention is significantly higher than that of Comparative Example 1 without tin, and also higher than that of Comparative Example 2 using conventional palladium activation. Analysis suggests that the introduction of tin alters the microstructure and phase composition of the alloy, while the palladium-free pre-plating nickel process provides a large number of uniform nucleation sites, resulting in a grain refinement strengthening effect, thereby effectively improving the hardness of the coating.

[0054] Experimental Example 2 To further characterize the microstructure and composition of the alloy coating, the micromorphology of the alloy coating prepared in Example 3 was observed using a scanning electron microscope (SEM, model: JCM 7000); at the same time, its elemental distribution and content were analyzed using an energy dispersive spectroscopy (EDS).

[0055] Figure 3 This is a SEM image of the alloy coating obtained in Example 3. Figure 3 (a) is the SEM image at a scale bar of 20 μm. Figure 3 (b) in the image is the SEM image at a scale bar of 10 μm. Figure 3 As can be seen, the coating surface is uniform and dense, without obvious defects such as cracks or pinholes. This coating structure helps to block the penetration of external corrosive media, thus providing a good physical barrier and a solid foundation for the corrosion resistance of the PCB copper-clad laminate.

[0056] EDS was used to perform surface scanning analysis on the micro-area of ​​the alloy coating obtained in Example 3, and the elemental distribution map of the alloy coating obtained in Example 3 was obtained, as shown below. Figure 4 As shown; Figure 4 In the figure, 'a' represents the comprehensive distribution map. Figure 4 In the diagram, 'b' represents the distribution of nickel (Ni) element. Figure 4 In the diagram, 'c' represents the distribution of phosphorus (P). Figure 4 In the diagram, 'd' represents the distribution of tin (Sn) elements. (From...) Figure 4 As can be seen, nickel (Ni), tin (Sn), and phosphorus (P) exhibit a uniform and dispersed distribution on the coating surface, without localized agglomeration or obvious phase separation. This uniform elemental distribution confirms that the method of the present invention can effectively induce a stable nickel-tin-phosphorus ternary alloy co-deposition process after palladium-free pre-plating nickel activation.

[0057] Further semi-quantitative compositional analysis was performed based on the EDS surface scanning area, and the content of each element in the coating is shown in Table 1.

[0058] Table 1. Element content in the coating

[0059] As shown in Table 1, the Ni content in the coating is 90.70 wt%, the P content is 6.85 wt%, and the Sn content is 2.44 wt%. Combined with the uniform element distribution and the above component ratios, it can be seen that the nickel-tin-phosphorus ternary alloy coating prepared by this invention not only has excellent appearance quality, but its reasonable element ratio also helps to meet multiple performance requirements such as high hardness, good corrosion resistance, and solderability.

[0060] In summary, this invention utilizes a palladium-free pre-plating nickel activation solution containing dimethylaminoborane to directly deposit a thin nickel layer with autocatalytic activity on the copper surface, completely replacing the palladium activation step in traditional electroless nickel plating processes. Subsequently, a nickel-tin-phosphorus ternary alloy coating is deposited on this pre-plated nickel layer. This invention eliminates the use of palladium, significantly reducing raw material costs and the burden of treating palladium-containing wastewater, resulting in good economic benefits and environmental friendliness. The obtained nickel-tin-phosphorus ternary alloy coating exhibits high hardness, good corrosion resistance, excellent solderability, and is uniform, dense, and strongly bonded to the copper substrate. The process steps of this invention are clear, easy to operate, and highly adaptable, suitable for large-scale production lines in the PCB industry, providing a low-cost, high-performance, and environmentally friendly new solution for PCB surface treatment.

[0061] Finally, it should be noted that the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for palladium-free electroless plating of nickel-tin-phosphorus alloy on copper-clad laminates of PCBs, characterized in that, Includes the following steps: S1. Immerse the PCB copper-clad board in a palladium-free pre-plating nickel activation solution for pre-plating nickel to obtain a PCB copper-clad board with a nickel layer; the palladium-free pre-plating nickel activation solution includes dimethylaminoborane. S2. Immerse the PCB copper-clad board with a nickel layer into a chemical nickel-tin-phosphorus plating solution for chemical plating treatment to obtain a PCB copper-clad board with a nickel-tin-phosphorus ternary alloy plating layer deposited on it.

2. The method according to claim 1, characterized in that, In S1, the palladium-free pre-plated nickel activating solution comprises the following components: nickel sulfate 20-40 g / L, boric acid 20-30 g / L, ammonium chloride 20-30 g / L, citrate 20-40 g / L, and dimethylaminoborane 1-5 g / L.

3. The method according to claim 2, characterized in that, The citrate includes at least one of ammonium citrate and sodium citrate.

4. The method according to claim 1, characterized in that, In S1, the temperature of the pre-plating nickel treatment is 50-70℃, the pH is 7-9, and the time is 3-5 min.

5. The method according to claim 1, characterized in that, In S2, the electroless nickel-tin-phosphorus plating solution comprises the following components: nickel sulfate 20-40 g / L, sodium stannate 15-30 g / L, sodium hypophosphite 50-70 g / L, lactic acid 60-100 mL / L, gluconic acid 10-30 mL / L, and ammonium sulfate 50-80 g / L.

6. The method according to claim 1, characterized in that, In S2, the temperature of the electroless plating treatment is 45-55℃, the pH is 6.5-7.5, and the time is 10-20 min.

7. The method according to claim 1, characterized in that, In step S1, before immersing the PCB copper-clad laminate into the palladium-free pre-plated nickel activation solution, the PCB copper-clad laminate is further subjected to degreasing and micro-etching treatments in sequence.

8. The method according to claim 7, characterized in that, The degreasing treatment is carried out in a degreasing solution; the degreasing solution comprises the following components: sodium hydroxide 5-15 g / L, sodium carbonate 10-30 g / L, sodium silicate 5-10 g / L, and sodium phosphate 10-30 g / L; the degreasing treatment is carried out at a temperature of 60-70℃ for a time of 2-5 minutes.

9. The method according to claim 7, characterized in that, The micro-etching treatment is carried out in a micro-etching solution; the micro-etching solution comprises the following components: 10-20 g / L sulfuric acid solution and 20-40 g / L sodium persulfate; the temperature of the micro-etching treatment is 10-25℃ and the time is 30-60 s.

10. A copper-clad PCB fabric prepared by the method according to any one of claims 1-9, characterized in that, The surface of the copper-clad PCB has a nickel-tin-phosphorus ternary alloy plating formed by the method described above.